The Role of the Financial Services Authority in Supervision of Fraud Prevention in Life Insurance Companies in Indonesia - Iwan Adinugroho; Rusdiaman Rauf; Nyamin Sucipto (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to provide a monitoring strategy, especially in the field of preventing fraud in life insurance companies in Indonesia. The form of this research is qualitative and follows a normative approach by reviewing the duties, objectives, and authorities of the Financial Services Authority to prevent fraud in life insurance companies. The object of this research is a life insurance company that has been declared bankrupt by the Financial Services Authority, namely PT. Bumi Asih Jaya Life Insurance. The results of this study provide an overview of fraud prevention strategies at life insurance companies in the form of emphasis on supervision through the audit function, especially in the field of direct examination of reports made by life insurance companies and then matched with documents owned by insurance. Supervision must be carried out regularly and consistently.